Chemical Pulps for Writing and Printing Papers from Casuarina Equisetifolia - Guha, S. R. D.; Madan, R. N. (Indian Forester, 1963)
Laboratory experiments on production of chemical pulps from Casuarina equisetifolia for writing and printing papers by sulphate process are described. The average fibre length of the pulp was 1.08 mm and the average fibre diameter was 0.011 mm. Easy bleaching pulps in good yield with satisfactory strength properties could be prepared. The investigation reported in this paper has shown that C. equisetifolia is a promising fibrous raw material for the manufacture of white writing and printing papers.